Micronucleus count in nasal epithelial cells from patients with chronic rhinosinusitis and polyps - Drummond,Renata Loss (2020)
Abstract Introduction: Chronic rhinosinusitis with nasal polyps, a prevalent disease affecting around 2% of the world population, is characterized by symptomatic inflammation of the nasal mucosa and impairment of quality of life. Chronic rhinosinusitis with nasal polyps has a multifactorial etiology, involving a dysfunctional host response to environmental factors. Thus, inflammatory models may be useful to shed light on the pathophysiology of this disease. Micronucleus count has been used to screen DNA damage in various tissues. Objective: To investigate the association between frequency of micronucleus in exfoliated cells from the nasal cavity of patients with chronic rhinosinusitis with nasal polyps and disease severity. Methods: This cross-sectional study included 21 patients with chronic rhinosinusitis with nasal polyps and 19 controls without disease. None of the participants were smokers. Results: Mean micronucleus count was 3.690 per 1000 cells (±2.165) in individuals with vs. 1.237 per 1000 cells (±0.806) in controls; (Student's t test = 4.653, p< 0.001). Nasal surgery in the past 5 years and aspirin-exacerbated respiratory disease were not associated with nicronucleus count (p= 0.251). Conclusion: Micronucleus count seems to be linked to chronic rhinosinusitis with nasal polyps, providing a new perspective for the evaluation of this disorder.